2012
DOI: 10.1007/s00438-012-0724-6
|View full text |Cite
|
Sign up to set email alerts
|

The 5′ untranslated region of the soybean cytosolic glutamine synthetase β1 gene contains prokaryotic translation initiation signals and acts as a translational enhancer in plants

Abstract: Glutamine synthetase (GS) catalyzes the synthesis of glutamine from glutamate and ammonia. In plants, it occurs as two major isoforms, a cytosolic form (GS1) and a nuclear encoded chloroplastic form. The focus of this paper is to determine the role of the 5′UTR of a GS1 gene. GS1 gene constructs with and without its 5′ and 3′ UTRs, driven by a constitutive promoter, were agroinfiltrated into tobacco leaves and the tissues were analyzed for both transgene transcript and protein accumulation. The constructs were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 54 publications
1
12
0
2
Order By: Relevance
“…3C) suggests post-transcriptional regulation of GS1 transcripts in plants exposed to high ammonium. The 59-UTR of Gln-1;3 may function as a translational enhancer (Ortega et al, 2012) and may have contributed to the increase in GS1 protein in the gln1;2 and gln1;1:gln1;2 knock-out lines under the high ammonium conditions. Post-transcriptional and post-translational regulation may have been involved in maintaining the level of GS2 protein (Fig.…”
Section: Responses Of Gs Protein and Activity To High Ammonium Levelsmentioning
confidence: 99%
“…3C) suggests post-transcriptional regulation of GS1 transcripts in plants exposed to high ammonium. The 59-UTR of Gln-1;3 may function as a translational enhancer (Ortega et al, 2012) and may have contributed to the increase in GS1 protein in the gln1;2 and gln1;1:gln1;2 knock-out lines under the high ammonium conditions. Post-transcriptional and post-translational regulation may have been involved in maintaining the level of GS2 protein (Fig.…”
Section: Responses Of Gs Protein and Activity To High Ammonium Levelsmentioning
confidence: 99%
“…The regulation of GS 1 gene expression is not limited to transcription (Sengupta‐Gopalan & Ortega, ). It has been shown that GS 1 is regulated at the level of transcript stability, mediated by its 3′UTR (Ortega et al., ; Simon & Sengupta‐Gopalan, ) and at the translational level by the 5′UTR (Ortega, Wilson, & Sengupta‐Gopalan, ). Furthermore, GS is subject to extensive posttranslational modification like phosphorylation (Finnemann & Schjoerring, ; Lima, Seabra, Melo, Cullimore, & Carvalho, ), ubiquitination, and binding with other proteins (Seabra, Silva, & Carvalho, ).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the 5'-UTRs and their influence on the efficiency of gene expression is being studied intensively [8,9]. Basically, comparative studies of 5'-UTRs of various genes are being conducted using reporters [10,11]. It was demonstrated in these studies that the nucleotides in the 5'-UTR, located above the start codon, significantly affect the level of translation initiation in eukaryotes, including plants [12].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, elements located below the transcription start codon that can control the transcription [6] or translation [15], as well as both transcription and translation [16], were identified. However, the structure and composition, as well as the role of such regulatory sequences, controlling gene expression particularly in plants are still poorly studied [11,14]. A variety of functions and opposite effects of CpG dinucleotides in regulatory and coding regions of eukaryotic genes allows making the assumption that they may play a key role in the regulation of gene expression [6,15,17].…”
Section: Introductionmentioning
confidence: 99%